SEI layer formation on amorphous si thin electrode during precycling - Lee, Yong Min; Lee, Jun Young; Shim, Heung-Taek; Lee, Joong Kee; Park, Jung-Ki (ELECTROCHEMICAL SOC INC, 2007)
The morphological and compositional changes of the solid electrolyte interphase (SEI) layer formed on the surface of Si thin electrodes during precycling were investigated. At the beginning of charging, the native layer (SiO2 and silanol) covering the surface of the Si thin electrode is readily destroyed and a new SEI layer is formed by the decomposition of both organic solvents and anions. At this stage, the interfacial resistance decreases to a minimum level. Thereafter, the interfacial resistance increases with charging due to the growth of an SEI layer, which is mainly originated from the decomposition of organic solvents. During the discharging process, an SEI layer was formed mainly by the decomposition of anions. (c) 2007 The Electrochemical Society.
Keywords: ANODE